Electromagnetic Radiation: Variational Methods, Waveguides and Accelerators - Milton, Kimball A.; Schwinger, Julian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
This is a graduate level textbook on the theory of electromagnetic radiation and its application to waveguides, transmission lines, accelerator physics and synchrotron radiation. It has grown out of lectures and manuscripts by Julian Schwinger prepared during the war at MIT's Radiation Laboratory, updated with material developed by Schwinger at UCLA in the 1970s and 1980s, and by Milton at the University of Oklahoma since 1994. The book includes a great number of straightforward and challenging exercises and problems. It is addressed to students in physics, electrical engineering, and applied mathematics seeking a thorough introduction to electromagnetism with emphasis on radiation theory and its applications. A hardcover edition containing additionally the reprints of more than 15 papers by Schwinger on these topics is available separately.
Maxwell$1 (Bs Equations -- Spherical Harmonics -- Relativistic Transformations -- Variational Principles for Harmonic Time Dependence -- Transmission Lines -- Waveguides and Equivalent Transmission Lines -- Rectangular and Triangular Waveguides -- Electromagnetic Fields in Waveguides with Circular Cross Sections -- Reflection and Refraction -- Variational Methods -- Examples of Variational Calculations for Circular Guide -- Steady Currents and Dissipation -- The Impedance Concept in Waveguides -- Accelerators: Microtrons and Synchrotrons -- Synchrotron Radiation -- Diffraction -- Quantum Limitations on Microwave Oscillators.s
Keywords: Physics; Optics; Electrodynamics; Particle acceleration; Electrical engineering; Physics; Optics and Electrodynamics; Mathematical Methods in Physics; Particle Acceleration and Detection, Beam Physics; Electrical Engineering; Electronic books